Adjusting to Trade-Policy Changes in Export Markets : Evidence from U.S. Antidumping Duties on Vietnamese Catfish - Brambilla, Irene (2012)
A large literature studies the effects of trade policy changes on developing-country exports on household incomes, and recent contributions have increasingly addressed the effects of administered protection, such as anti-dumping duties. In 2003 the United States imposed anti-dumping tariffs on imports of catfish from Vietnam ranging from 37 to 64 percent. As a result, Vietnamese exports of catfish to the U.S. market declined sharply, thus providing a unique opportunity to study the effects of U.S. trade policy changes on Vietnamese families. Using data on Vietnamese households, the authors study the responses of catfish producers in the Mekong delta of Vietnam between 2002 and 2004. The evidence suggests that the rate of growth of income of households that depended on catfish sales was significantly affected. In addition, the anti-dumping duties triggered significant exit from catfish farming. Households adjusted by moving out of catfish aquaculture and into wage labor markets and agriculture, but not into other aquaculture activities. Finally, the evidence also suggests that households found it difficult to change their catfish production levels, and that performance in aquaculture affects other household economic activities.